Implementation of Halal Causation Against the Sale and Purchase of Collateral Objects without the Approval of Creditors - Adi Murphi Malau; Syafrinaldi Syafrinaldi; Lina Jamilah (Borong Newinera Publisher, 2022)
The sale and purchase is known as novation as long as the sale and purchase is carried out by the debtor with written approval from the bank as the creditor, but in practice the sale and purchase of collateral objects by the debtor to a third party without the approval of the bank as the creditor sometimes also occurs and causes problems in the future. This study aims to provide a prescription regarding the implementation of a lawful cause for the legality of the deed of sale and purchase of land by the debtor without the approval of the creditor. This research method is a normative legal research, using a statutory approach, a conceptual approach, and a case comparison approach, the case used in this research is the District Court Decision Number 7/Pdt.G/2019/PN.Rhl which is confirmed by the Court's Decision Pekanbaru High Court with Case Number 85/PDT/2020/PT PBR was further reaffirmed by the Supreme Court of the Republic of Indonesia with Decision Number: 1600 K/Pdt/2021 so that it has permanent legal force or inkracht.